Theologia magistra philosophiae. Un ejemplo: la lectura teológica de la naturaleza y el naturalismo filosófico en el siglo XII. - LÁZARO, MANUEL (Anuario Filosófico, 2014)
The present article presents the possibility of a dialogical and fruitful relation between philosophy and theology, over and against criticisms of Christian thought that have arisen in some postmodern antihuma-nist circles. It intends to show that theology acts as "magistra" for philosophy in a Socra-tic sense: it helps to form the philosopher's soul in a Socratic manner. This historic-doctrinal reality can be traced in a number of topics in the history of philosophy, which are in dialogue with realities that have arisen from revelation, such as the theology of creation, sacramental theology or the dogma of incarnation. In particular, the contribution of theology to philosophy concerning the study of "nature" in the 12th century is presented as an example.